A general medical short‐stay unit is not more efficient than a traditional model of care. Issue 8 (1st May 2014) - Russell, Patrick T; Hakendorf, Paul; Thompson, Campbell H
Abstract: Objectives: To assess the efficiency of a short‐stay unit (SSU) for undifferentiated medical patients and evaluate its effect on the overall efficiency of a general medicine department. Design, setting and patients : Retrospective study of all general medical patients admitted to the SSU at Flinders Medical Centre, South Australia, during its 5 years of operation (2005–2009), compared with 4 years before its institution and 2 years after its closure. Main outcome measures: Relative stay index (RSI); inhospital mortality; readmissions within 7 and 28 days. Results: 23 790 general medical patients were admitted overall, and 10 764 of these (45.2%) were admitted to the SSU. The RSI for the SSU during its years of operation was 0.79, compared with 1.34 for the long‐stay unit. The overall RSI for the department did not improve during those years and was not significantly different to the periods before or after. Conclusions: We found no evidence that an SSU for undifferentiated medical patients creates bed capacity. It does, however, appear to be safe.